Supply chain integration of shipping companies - Panayides, Photis; Wiedmer, Robert; Andreou, Panayiotis; Louca, Christodoulos (My University, 2012)
Integration and consolidation have characterized the container shipping industry primarily as a means to gain economies of scale and cost efficiencies. In previous years, liner companies invested in increasing vessel capacities in order to maintain profit margins. Considering the large investments in container vessels, only a high utilization of the companies’ assets guarantees profitability. Consequently, the slump in maritime trade affects the profitability of liner shipping companies. Vessel capacity provides only one possibility for competitiveness. Possible ways to elude this situation are to minimize investments in capital-intensive vessels or to avoid a high dependency on liner services by diversification of a company’s service portfolio and the integration of logistics services, respectively. Vertical integration is characterizing the modern transport industry, as transport businesses are gearing up towards global logistics services based on the principle of the ‘one-stop-shop.’ In order to accomplish this goal, it is necessary to integrate port, hinterland transportation, and logistics management services. It follows that strategic aspects of vertical integration are of significant importance in the contemporary shipping industry. The aim of this chapter is to theoretically explain the importance of vertical integration in the supply chain by maritime companies and to investigate the performance outcomes of integration through an empirical investigation between supply chain integration and firm value.